Evaluating the Side Effects of COVID-19 Vaccines Available in Al-Diwaniyah Province - Meraim Attyah Kazaal; Roaa Abid Jaythoom; Noor Dakil Mahdi; Doaa Yousief Mohammed (Medical Journal of Babylon)
Background:Vaccines are critical to reducing the viral attack by permitting the body to generate a safe immune response that defends it by preventing or limiting infection. Objectives: The study aimed to detect the side effects that caused by immunization with Coronavirus (COVID-19) vaccines. Materials and Methods:286 samples were collected from individuals immunized with Corona vaccines (Pfizer, Sinopharm, and AstraZeneca) of different ages, whether they were previously infected with COVID-19 or not. The side effects and pathological complications of immunization have been clinically determined by specialized doctors. Results:Pfizer vaccine was the most used vaccine, yet its typical side effects of first dose include mild fever (28%) and injection site pain (20%). The second dose side effects of Pfizer vaccine were high fever in 200/246 people (81%). Moreover, 7% of the cases did not experience side effects after both doses. The first dose of Sinopharm vaccine side effects were pain in the area of the injection (30%) and mild fever (19%), and 8% of cases suffered from fever and pain in the head and joints, whereas high fever was one of the most prominent signs when taking the second dose by (51%) whereas 27% of them did not show any side effects when taking the two doses. Only three individuals were immunized with AstraZeneca vaccine and suffered from fever, headache, and joint pain after taking the first dose, whereas two of them were suffering from high temperature, and one was suffering from fatigue and joint pain after taking the second dose. Conclusion:The symptoms of COVID-19 vaccines are as the same as other vaccines, but still needs more studies analyzing their side effects to ensure their safety for immunization.